Anti-Covid antibody status in health care professionals of Bangladesh after 3 months of completion of two doses of Covid-19 vaccination - Nesa, Ayatun; Rahman, Kazi Muhammad Mahbubur; Ali, Abdul; Yesmin, Roksana (Bangladesh Journal of Medicine, 2023)
Background: Coronavirus 2019 (COVID-19) is a pandemic disease, where huge number of populations was infected, and massive death occurred worldwide for its rapid spread. Naturally produced antibody or artificially given vaccination can only give protection.This study evaluated the anti-Covid antibody status in health care professionals of Bangladesh after 21 days and 3 months of completion of two doses of Covid-19 vaccination. Methods: This study was conducted at the Department of Laboratory Medicine, BIRDEM, Dhaka. Total 100 respondents who had completed two doses of Covid-19 vaccinationwere enrolled according to inclusion criteria. After taking informed written consent a structured questionnaire was filled up for each subject. First sample (3 ml whole blood) was collected after 21 days of completion of 2nd doses of SARS-CoV-2 vaccination and a 2nd sample (3 ml whole blood) was collected again after 3 months.SARS-CoV-2 IgG was estimated by indirect chemiluminescence assay. Collected data were analyzed by SPSS 22. Results: The mean age of the study subjects was 32.09 ± 7.98. Study subjects were divided into two groups: those with history of past Covid infection (PCR positive) (n=33) and those with no evidence of past infection (n=67). SARS-CoV-2 IgG antibody level was found significantly reduced after 3 months of completion of vaccination, compared to the titer of 21 days of vaccination. A significant difference of mean SARS-CoV-2 IgG antibody level among subjects with and without previous history of Covid 19 infectionwas observedafter 21 days of completion of 2nd dose of Covid 19 vaccination. However, after 3 months of 2nd dose of vaccination no significant differences ofmean SARS-CoV-2 IgG antibody level were observed between the groups. Conclusion: SARS-CoV-2 IgG antibody level was significantly reduced after 3 months of completion of two doses of vaccination. Moreover, antibody level was found significantly higher among the study subjects with previous positive H/O of Covid 19 infection compared to subjects without any H/O previous Covid infection. Therefore, this study recommended that, a third booster dose would be necessary to maintain the effectiveness of vaccines. Bangladesh J Medicine 2023; 34(2): 80-85